Calcium: Chemistry, Analysis, Function and Effects 2015
DOI: 10.1039/9781782622130-00030
|View full text |Cite
|
Sign up to set email alerts
|

Food Sources of Calcium Vary by Ethnicity and Geography

Abstract: Sources of dietary calcium vary worldwide. Dairy is included in European, Middle Eastern, and South Asian cuisines; however, it is not a part of traditional Polynesian cuisines, nonpastoral African cuisines, the cuisines of the indigenous peoples of the Americas, or most Asian cuisines. Westernization has resulted in increased dairy intake among many ethnic groups that did not historically consume it. Although dairy is often the top source of calcium where it is consumed, it does not always provide the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, several studies have reported that the calcium content increased by up to 400% of that in corn grains [ 6 , 7 ], as well as its bioavailability, due to the Ca[OH] 2 added during the cooking process. Nixtamalized products represent a significant source of calcium for many Latin American populations [ 8 ], as demonstrated in a study conducted with Mexican women who consumed nixtamalized tortillas for 12 days [ 9 ]. Calcium absorption showed a 25-fold increase compared with women who consumed non-nixtamalized tortillas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have reported that the calcium content increased by up to 400% of that in corn grains [ 6 , 7 ], as well as its bioavailability, due to the Ca[OH] 2 added during the cooking process. Nixtamalized products represent a significant source of calcium for many Latin American populations [ 8 ], as demonstrated in a study conducted with Mexican women who consumed nixtamalized tortillas for 12 days [ 9 ]. Calcium absorption showed a 25-fold increase compared with women who consumed non-nixtamalized tortillas.…”
Section: Introductionmentioning
confidence: 99%